Comparative study of the post-Olympiad economic strategy of previous Olympic games - Wang, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The Olympic economy is a unique economic phenomenon. It moves forward with a massive people stream, financing stream and information stream. The nature of the Olympic economy is therefore likened to "attention economy". If the post-Olympiad economy comes forth with the "siphon effect", it will increasingly pull down the economy. The purpose of this paper is to perform a comparative analysis of the strategies used by previous Olympic Games and the post-Olympiad economy. It also presents an analytical review of the respective strategies in order of precedence, and points out their experiences and lessons which the Beijing Olympiad can take for reference.